TUTURAN WARGANET TERHADAP KASUS PELECEHAN SEKSUAL PENYANYI VIA VALLEN DALAM KOLOM KOMENTAR DI INSTAGRAM (KAJIAN PRAGMATIK) - Shinta Yunita Tri Nuraeni (Universitas Sultan Ageng Tirtayasa, 2021)
The problem described in this paper is the function of speech acts and the resulting conversational implications of netizens speech on cases of sexual harassment by singer Via Vallen in the comments column on Instagram. Based on this problem, the purpose of this study is to explain and classify the function of speech acts and the resulting conversational implications of netizens utterances regarding cases of sexual harassment by singer Via Vallen in the comments column on Instagram. The data were collected using the observation method and notetaking technique. Data were reviewed and analyzed using contextual methods. Presentation of the results of the analysis was carried out using informal methods. The results of the analysis found five speech act functions, namely the function of declaration, representation, expressiveness, directive, and commissive. Conversational implicatues found four conversational implicatures, namely conversational implicatures as a result of violations of the maxims of quantily, quality, relevance, and implementation.